Representations and warranties - Matias, Sofia Araújo (2021)
The purpose of this paper is to study the Representations and Warranties, clauses from Anglo-Saxon legal systems which have been gaining prominence in company purchase and sale agreements in Portugal. This inclusion is not without difficulties, so this paper tries to portray the problems, and possible solutions, from its origin to the application in our legal system.